7 - Book Reviews - SIMSON, Howard (Africa Development, 1983)
South Africa — A Model Capitalist State ? David Yudelman: The Emergence of Modern South Africa — State, Capital, and the Incorporation of Organized Labour on the South African Gold Fields, 1902-1939, Greenwood Press. Dan O'Meara: Volkskapitalisme — Class, capital and ideology in the develop ment of Afrikaner nationalism, 1934—1948. Cambridge University Press and Ravan Press. Dr. Howard SIMSON, See Howard Simson «The Social Origins of Afrikaner Fascism and its Apartheid Policy »,Uppsala Studies in Economic History, 21 Almquist & Wiksell International. Stockholm